2012
DOI: 10.1111/j.1600-0463.2012.02931.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of snail, twist, and Zeb1 in malignant mesothelioma

Abstract: We examined 56 malignant mesotheliomas, 117 lung adenocarcinomas, and 34 metastatic lung adenocarcinomas with antibodies to transcription factors involved in epitheliomesenchymal transition. The tumors were stained immunohistochemically with antibodies zeb1, twist, and snail. Malignant mesotheliomas exhibited a stronger expression of zeb1 and twist than lung adenocarcinomas (p < 0.001 for both). Metastatic adenocarcinomas displayed a more frequent expression of zeb1 and twist (p < 0.001 for both) than lung ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
101
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(106 citation statements)
references
References 31 publications
3
101
0
Order By: Relevance
“…First, positive expression of all of the EMT-related molecules (except fibronectin) was frequently expressed, similar to mesothelin [19] and osteopontin [20], in patients with MPM. Vimentin, Twist and YB-1 (mesenchymal markers) had a tendency to be slightly increased in sarcomatoid tumors compared to epithelioid tumors, which was consistent with the results of previous studies [10,11]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…First, positive expression of all of the EMT-related molecules (except fibronectin) was frequently expressed, similar to mesothelin [19] and osteopontin [20], in patients with MPM. Vimentin, Twist and YB-1 (mesenchymal markers) had a tendency to be slightly increased in sarcomatoid tumors compared to epithelioid tumors, which was consistent with the results of previous studies [10,11]. …”
Section: Discussionsupporting
confidence: 82%
“…Few studies have evaluated the prognostic value of EMT markers in MPM [8,9,10,11]. We hypothesized that the mesenchymal characteristics might predominate in the epithelioid-type tumors, and that the deregulated EMT status may indicate aggressive behavior in MPM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that epithelioid MPM had a higher level of expression of E-cadherin than the biphasic and sarcomatoid subtypes (52)(53)(54). However, the absence of E-cadherin expression in some subgroups of epithelioid MPM tumors despite their epithelial histologic features was previously observed by immunohistochemistry (52,54). In these studies, E-cadherin staining varied between 40% and 60%, which is in agreement with our classification of epithelioid MPM.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the molecular profile of the epithelioid MPM in the C2 subgroup, it may be suggested that these cells have undergone mesenchymal differentiation and acquired mesenchymal features, while still retaining some epithelial characteristics. Previous studies showed that epithelioid MPM had a higher level of expression of E-cadherin than the biphasic and sarcomatoid subtypes (52)(53)(54). However, the absence of E-cadherin expression in some subgroups of epithelioid MPM tumors despite their epithelial histologic features was previously observed by immunohistochemistry (52,54).…”
Section: Discussionmentioning
confidence: 62%
“…Twist expression was previously shown in some normal tissues such as prostate and breast (11,19). it was also demonstrated that this protein showed higher expression in malignant tumors compared to benign tumors such as prostate, parathyroid and lung (19)(20)(21). in the salivary gland tumors, there has been some investigation on Twist expression in adCCs and Pa.…”
mentioning
confidence: 99%